Design, analysis and verification of hexagon split ring resonator based negative index metamaterial - Bose, Sumanta (2014)
This paper proposes the design of a Hexagon Split Ring Resonator (HSRR) with skew angle rotation between inner and outer ring. Mathematical expressions for the resonant frequency of HSRR are formulated. The CAD model of the HSRR is analyzed for electric and magnetic fields in a finite element (FEM) method mode solver based fields in a finite electromagnetic simulator and its scattering parameters are obtained. The dips and crossings in the S-parameters are used to plot the refractive index versus frequency, which verifies its Negative Refractive Index Material (NRIM) property in certain frequency bands.